A stochastic planning model for humanitarian relief response logistics. (2016) - Safeer, M.; Anbuudayasankar, S.P.; Saleeshya, P.G.; Ganesh, K.
During emergencies, decision making to support relief preparedness and response activities are challenging task requiring quick and effective action from responders under uncertainty conditions. This paper proposes a response planning stochastic model for humanitarian transportation operations. The objective of this proposed model is to minimise total transportation duration during emergency situations. This model aims to maximise satisfaction levels through attaining quick response which can help in making decisions on disaster relief logistics.